Peningkatan Hasil Belajar Servis Bulu Tangkis melalui Latihan Target Sasaran pada Siswa Kelas VII-D SMPN 1 Kediri - Dedi Pardiansyah; Mokhammad Firdaus; Danang Kanda Riyatmojo (CV. KAMPUS AKADEMIK PUBLISING, 2025)
This study aims to improve badminton service learning outcomes through target training for Grade VII-D students at SMP Negeri 1 Kediri. The method used is Classroom Action Research (CAR), which consists of two cycles with stages of planning, implementation, observation, and reflection. The research instruments include observation, skill tests, interviews, and questionnaires, with data analyzed using descriptive quantitative and qualitative methods. The results show that target training significantly improves students' service skills, particularly in accuracy, consistency, technique, and shot power. This method also enhances students' confidence and motivation in learning badminton. Target training has proven effective in helping students understand the correct service technique and improving their motor skills. The study's implications indicate that a structured training-based approach can be applied in physical education to optimize students' learning outcomes. Therefore, physical education teachers are encouraged to use target training methods in badminton learning to enhance instructional effectiveness and student achievement.